1991
DOI: 10.1152/ajpregu.1991.261.1.r20
|View full text |Cite
|
Sign up to set email alerts
|

Renal denervation does not prevent hypertension in Lyon hypertensive rats

Abstract: The effects on blood pressure (BP) of a single and repeated renal denervations (RD) were compared in genetically hypertensive (LH) and normotensive (LN) rats of the Lyon strain. Indirect BP was measured by the tail-cuff method, and direct BP was measured through an aortic catheter in conscious quiet rats receiving a normal-sodium diet. Single RD (10 wk of age) did not reduce BP in both LN and LH rats. Repeated RD (4, 7, and 10 wk of age) partly prevented the age-related increase in tail-cuff BP but did not aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that renal denervation prevents or attenuates some forms of genetic and experimental hypertension in animals such as spontaneously hypertensive rats, 22,23 New Zealand genetically hypertensive rats, 24 2-kidney models of Goldblatt hypertensive rats, 25 lowsodium, 1-kidney hypertensive rats, 26 angiotensin-induced hypertensive rats, 27 and obesity-induced hypertensive dogs, 28 although negative results were reported in Dahl salt-sensitive rats 31 and Lyon hypertensive rats 32 and conflicting results were also obtained in hypertensive models induced by aortic coarctation, 33,34 NO synthase inhibition, 35,36 and deoxycorticosterone acetate salt treatment 37,38 and in the 1-kidney model of Goldblatt hypertensive rats. 39,40 In the present study, bilateral RD depleted the renal tissue NE content by 94% (measured at the end of the experiments, ie, 2 to 4 weeks after RD), suggesting that the denervation procedure was effective and that significant reinnervation had not yet occurred.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that renal denervation prevents or attenuates some forms of genetic and experimental hypertension in animals such as spontaneously hypertensive rats, 22,23 New Zealand genetically hypertensive rats, 24 2-kidney models of Goldblatt hypertensive rats, 25 lowsodium, 1-kidney hypertensive rats, 26 angiotensin-induced hypertensive rats, 27 and obesity-induced hypertensive dogs, 28 although negative results were reported in Dahl salt-sensitive rats 31 and Lyon hypertensive rats 32 and conflicting results were also obtained in hypertensive models induced by aortic coarctation, 33,34 NO synthase inhibition, 35,36 and deoxycorticosterone acetate salt treatment 37,38 and in the 1-kidney model of Goldblatt hypertensive rats. 39,40 In the present study, bilateral RD depleted the renal tissue NE content by 94% (measured at the end of the experiments, ie, 2 to 4 weeks after RD), suggesting that the denervation procedure was effective and that significant reinnervation had not yet occurred.…”
Section: Discussionmentioning
confidence: 99%